High-resolution characterization of gene function using single-cell CRISPR tiling screen - Lu Yang (Nature Portfolio, 2021)
Identifying functional domains and genetic regulatory mechanisms is essential for developing new therapies. Here the authors present sc-Tiling, single-cell high-density CRISPR tiling screening for functional domain characterization.